Impact of baseline IOP, vacuum, and different docking mechanisms, and their interaction on IOP rise in femtosecond laser‐assisted refractive and cataract surgery. Issue 12 (December 2019) - Mariacher, Siegfried; Laubichler, Peter; Mariacher, Martina; Wendelstein, Jascha; Fischinger, Isaak; Bolz, Matthias
Abstract : Purpose: : To study the intraocular pressure (IOP) variation during vacuum and docking of femtosecond laser application. Setting: : Department for Ophthalmology, Kepler University Hospital, Johannes Kepler University Linz, Austria. Design: : Experimental study. Methods: : Intracameral intraocular pressure (IOP) was monitored in 30 porcine ex vivo models using a dual femtosecond laser platform (VICTUS). Five different baseline IOP levels (10 to 30 mm Hg) were assessed during fluid‐filled (liquid) docking, full‐contact (applanating) docking, and vacuum application without docking. Results: : Raising the baseline intracameral IOP from 10 to 30 mm Hg increased the IOP from 27.55 mm Hg ± 5.93 (SD) to 56.85 ± 6.10 mm Hg in the fluid‐filled docking group, and from 60.91 ± 8.41 mm Hg to 90.11 ± 6.64 mm Hg in the full‐contact docking group. The full‐contact docking procedure per se (excluding vacuum effect) increased the IOP by 61.7% (+36.58 ± 5.84 mm Hg). In contrast, fluid‐filled docking (excluding vacuum effect) raised the IOP by only 3.1% (+0.72 ± 2.71 mm Hg). Each 5 mm Hg reduction of baseline IOP resulted in a mean IOP reduction of 7.33 ± 3.05 mm Hg in the fluid‐filled group, and 7.30 ± 6.88 mm Hg in the full‐contact docking group ( P < .001). Decreasing baseline intracameral IOP from 15 to 10 mm Hg resulted in the highest IOP reduction between all subgroups ( P < .01). Conclusions: : Baseline IOP, docking procedures, and vacuum influenced IOP during femtosecond laser application in a synergistic manner. Lowering the baseline intracameral IOP resulted in a significantly lower IOP during fluid‐filled docking for cataract surgery and full‐contact docking for refractive surgery. Full‐contact (applanating) docking resulted in a significantly higher IOP elevation compared with similar IOP values found during fluid‐filled (liquid) docking and the application of the suction ring alone without docking.